Calcidius on Plato's Timaeus: Greek philosophy, Latin reception, and Christian contexts - Reydams-Schils, Gretchen J. (Cambridge University Press, 2020)
"Introduction Beyond the Calcidius Pass It would be difficult to overestimate the importance of Calcidius' work on Plato's Timaeus, which consists of a partial Latin translation and commentary.1 So many links in the extensive commentary tradition of the Timaeus are no longer extant. We have snippets from Crantor, a mere allusion (and a highly debated one at that) to a possible commentary by Posidonius,2 part of a translation by Cicero, allusions to Adrastus' commentary, a commentary by Theon of Smyrna that deals only with the mathematical issues, and a mere shadow of Porphyry's commentary, to name but some. Because of these lacunae Calcidius' work becomes all the more valuable. Moreover, Calcidius presents one of those very rare cases of a Latin philosophical commentary. As the knowledge of Greek started to wane at the end of Antiquity, Calcidius became one of the main channels through which Plato's legacy was transmitted to the Middle Ages.3 Indeed, his work is one of the four master-texts of that era, as É. Jeauneau points out (1975: 30), together with Boethius' On the Consolation of Philosophy, Macrobius' commentary on Cicero's Dream of Scipio, and Martianus Capella's On the Marriage of Philology and Mercury"--